Evaluation of some quality characteristics of coated seeds with internal and foreign synthesized polymers on sugar beet, corn and alfalfa - Dariush Taleghani; Saeid Sadeghzadeh Hemayati; Farahnaz Hamdi Holasoo; Mehdi Sadeghi-shoae (علوم و فناوری بذر ایران, 2020)
The use of various types of polymers in the field of seed processing (coating seeds of various types of plants) has become very important in recent years. Polymer materials are used to add a mixture of fungicides and pesticides and growth regulators to help protect plant seedlings from growing and deploying better against pathogens and harmful insects in the early stages of plant growth. This research was carried out with the aim of making internal polymer and its feasibility study in seed of three sugar beet, corn and alfalfa crops during the years of 2014-2015. In order to compare the effect of foreign and internal polymer, seed quality, germination, abnormality percentage, Radicle length in laboratory and Seed vigor in greenhouse were evaluated. The results of the obtained spectra and surface tension the comparison of the polymer prepared with the foreign polymer used as a control. It can be concluded that the internalized polymer is physically and mechanically similar to that of an external polymer. Application of polymer in sugar beet cover had no adverse effect on germination and seed establishment. The results of this study showed that the synthesized internal polymer in this study can be used to coating the seeds of sugar beet and alfalfa and 1% and 1.5% for corn seeds in order to achieve optimum seed coating and not to have an adverse effect on their qualitative traits.